From safety to health : the New Zealand legal response on work-related psychosocial harm : a thesis presented in partial fulfilment of the requirements for the degree of Masters in Business Studies (MBS) at Massey University, Distance, New Zealand - Oosthuizen, Luzanne (Massey University, 2020)
Despite the widespread international acknowledgement that psychosocial hazards are an important health risk for workers, work-related psychosocial harm still remains relatively unexplored in New Zealand. The limited research within this field continues to focus on the potential underlying reasons for regulation difficulties. A portion of this field that has received considerably less attention is how psychosocial harm at the workplace is recognised in law. Therefore, this research aimed to explore the legal response in New Zealand to work-related psychosocial harm. This was undertaken by examining 24 court case transcripts retrieved from the New Zealand Legal Information Institute (NZLII) database. This unique and valuable data source provided information on cases that would otherwise be challenging to access. The data were selected from the year 2003 onward following the enactment of the Health and Safety in Employment Amendment Act (HSE Amendment Act) 2002. Transcripts were limited to the Employment Relations Authority (ERA), the Employment Court, and the New Zealand Health and Safety in Employment Decisions in which work-related psychosocial hazards were integral to the case being heard. The qualitative study’s findings, developed using the framework analysis methodology, demonstrated alignment with the regulatory requirements of sections 36, 44 and 45 of the Health and Safety at Work Act (HSWA) 2015. Further, findings uncovered the interrelated influence the Person Conducting a Business or Undertaking (PCBU), the officer (director, partner, or a person occupying a position comparable to that of a director), and the worker have in meeting legislative duties and contributing towards a healthy workplace. The study has concluded that, through analysing court case transcripts, sufficient evidence is available for the New Zealand regulator, WorkSafe NZ, to investigate and assess psychosocial harm at the workplace with the current legislation. Although amendments to the HSWA 2015 may be beneficial, it is not deemed essential for work-related psychosocial harm court prosecutions.
Keywords: 350507 Workplace wellbeing and quality of working life